Methanogenic bacteria in human vaginal samples. - Belay, N (1990)
Twelve vaginal samples were collected from separate patients, processed anaerobically, and added to methanogenic enrichment medium. Methanogenic activity was detected in two samples, both of which were from patients with bacterial vaginosis. None of the samples from healthy patients yielded positive methanogen cultures. One sample from a patient with bacterial vaginosis did not show any detectable methanogenic activity. Two methanogen isolates were obtained from one of the methanogen-positive samples, and both were identified as Methanobrevibacter smithii on the basis of morphological, cultural, and immunological features.